Penampilan Produksi Telur Burung Puyuh Yang Di Beri Tepung Daun Kelor ( Moringa Oleifera Lam ) Dalam Ransum - Ratna I Pabila; Nibras K Laya; Syukri I Gubali; Srisukmawati Zainudin (Gorontalo Journal of Equatorial Animals, 2023)
The present study aimed to determine the effect of Moringa leaf powder on the performance of quail (Coturnix coturnix Japonica) eggs production. The study was conducted from January to March 2022 at the production enclosures of the Department of Animel Science. Thelivestock used in the study were 100 quails, layer fase. Beside, the ration used was composed of feed ingrediens, namely moringa leaf powder, fish meal, concentrate,corn meal, rice bran, and premix. The study employed a completely randomized design (CRD) consisting of five treatments and four refilication. The treatments given in the study were P0: basic ration (withhout the addition of Moringa leaf flour), P1: 98% basic ration +2% Moringa leaf powder= 100%, P2:96% basic ration +4% Moringa leaf powder =100%, P3: 94% bsic ration + 6% moringa leaf powder =100%, P4: 92% basic ration + 8%Moringa leaf powder = 100%. Furthemore, the data obtained were analyzed using Analysis of Varians (ANOVA), and the variables observed were egg production , egg weight, ration consumption and ration conversion. The findings proved that the addition of Moringa leaf powder to quail rations provided for up to 35 days had no significant effect on egg production, egg weight, ration consumption, and ration conversion.